Sorry, but if I do your homework for you then you'll learn nothing.
2007-01-13 02:26:24
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
factor by applying looking something uncomplicated in the two aspects of the expression x(3) + 8y(3) 3(x+8y) now no rely if that's a cube then that's an entire nother ball of wax. DO YOU propose IT AS IS OR AS CUBED?
2016-12-12 10:29:23
·
answer #2
·
answered by Erika 4
·
0⤊
0⤋
x^3 + 8y^3 = (x+ay)(x^2 + bxy + cy^2)
x^3 + 8y^3 = x^3 +(a+b)x^2y + (ab+c)xy^2 + acy^3
a+b = 0
b=-a
ab + c = 0
a(-a) + c = 0
-a^2 +c = 0
a^2 = c
ac=8
a(a^2)=8
a^3 = 8
So, a = 2, b=-2, c = 4
x^3 + 8y^3 = (x+2y)(x^2 -2xy + 4y^2)
As x^2 -2xy + 4y^2 cannot be factored in real number,
x^3 + 8y^3 = (x+2y)(x - y(1+ sqrt(3)i))(x - y(1 - sqrt(3)i))
2007-01-13 02:42:25
·
answer #3
·
answered by seah 7
·
1⤊
0⤋
hint: it's the "sum of two cubes"
[ NOTE 8y^3 = (2y)^3 ]
X ^3+ Y^ 3 = (x + y)(X^ 2 - XY + Y ^2 ) <== "general 'form' " and NOT the "answer" buta good clue to HOW to get the answer
2007-01-13 02:43:31
·
answer #4
·
answered by atheistforthebirthofjesus 6
·
0⤊
0⤋
x^3+8y^3
(x+2y) (x^2-2yx+4y^2)
2007-01-13 02:34:59
·
answer #5
·
answered by SHIBZ 2
·
0⤊
0⤋
=x^3 +(2y)^3
this is in the form of a^3 +b^3 =(a+b)(a^2+ab+b^2)
=(x+2y)(x^2-2xy+4y^2)
2007-01-13 02:26:52
·
answer #6
·
answered by srinu710 4
·
1⤊
0⤋
y^3=x^3/8
then
y=3under root(x^3/8)
2007-01-13 02:28:03
·
answer #7
·
answered by Abdullah 2
·
0⤊
0⤋
x^3+8y^3
=x^3+(2^3)(y^3)
=x^3+(2y)^3
=(x+y)(x^2-xy+y^2)
2007-01-13 03:27:17
·
answer #8
·
answered by hirunisha 2
·
0⤊
0⤋
cube root the question. it will leave you with 3root x+8y.
2007-01-13 02:26:33
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
Just combine like terms (just add them).
2007-01-13 03:34:03
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋